Protomedicato in Peru - Zavala Batlle, Abraham (2010)
When Spain was the first World power, Protomedicato was established in the newly founded South American colonies. This word defines a Tribunal or College of King’s physicians, where medical students were examined and licensed. Before the Spanish arrived to South America, there was no regulating institution for Western medicine, so many persons claimedto be “doctors” and made good money from this. The Protomedicato Tribunal was created in Spain in 1442, and it was instituted in Peru in 1570, located in Lima. The first Peruvian medical officer was Dr. Francisco Bermejo y Roldan, who was born in Lima. This historical review complies and analyzes the history of Protomedicato in Peru.